Sustentabilidade de empreendimentos econômicos solidários: contribuições e desafios do PITCPES/UFPA a partir da análise da Cooperativa dos Fruticultores de Abaetetuba - COFRUTA - Silva, Anderson Roberto Pires e (2010)
The study aimed to understand how the methodology of hatching contributes to the sustainability of economic enterprises in solidarity. For analysis, we developed a study on the social economy and the incubation methodology, based on the program of teaching, research and extension - Technological Incubator of Popular Cooperatives and Entrepreneurship Solidarity (PITCPES), and as the survey of the Cooperative of Fruit of Abaetetuba - COFRUTA. We started from the exploratory-descriptive approach in a qualitative and quantitative, in order to demonstrate the process of sustainability under the dimensions of different kinds such as: the economic dimension, social dimension, the political dimension, size and scale management training. Based on the analysis of these different dimensions was reached results as: first the recognition that the incubator contributes to the sustainability of COFRUTA, especially with regard to planning, control and the need to diversify production. However, there was suggestion of cooperative for training and technical assistance is continued, to the extent that the performance of projects under the base leaves gaps for the learning and application of social technologies required to the Incubator. It also concluded that the dissertation contributes to the team of the incubator can assess their strengths and weaknesses in their performance